THE ROLE OF VITAMINS IN THE TREATMENT OF RHEUMATOID ARTHRITIS - Zh. V. Maximova; D. M. Maximov (SINAPS LLC, 2017)
It is well known that the inflammatory process in rheumatoid arthritis (RA) is mediated by free radicals. Antioxidant vitamins can neutralize oxidative cell damage, so they suggested alleviate symptoms and prevent progression of RA. This article provides an overview of a current literature about clinical role of the antioxidant vitamins in patients with RA. In general, only a few clinical trials focused on this issue, and just a high dose vitamin E supplementation demonstrated moderate clinical efficacy in RA. On the other hand, convincing evidence exist that Mediterranean diet, rich in antioxidants, may reduce inflammatory activity, increase physical functioning and improve general well-being. In conclusion, patients with RA should follow antioxidant-rich diet (grains, fruits, vegetables) rather than take vitamin supplementation.